2016
DOI: 10.1371/journal.pone.0165474
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Phacoemulsification Using Different Size of Clear Corneal Incision in Eyes with Previous Radial Keratotomy

Abstract: ObjectiveTo evaluate visual outcomes and complications after phacoemulsification in eyes with cataract and previous radial keratotomy (RK) cuts using different sizes of clear corneal incisions.MethodsThe study was a retrospective study. Thirty eyes with cataract and previous RK underwent phacoemulsification and intraocular lens (IOL) implantation. Among them 7 eyes had 8 RK cuts, 13 eyes had 12 RK cuts, and 10 eyes had 16 RK cuts. Phacoemulsification and IOL implantation were performed through a 2.0–3.2 mm cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…All cataract surgeries were performed by one surgeon (XH. W) using a clear corneal incision, phacoemulsification, and implantation of IOLs in the capsular bag according to our previous studies [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…All cataract surgeries were performed by one surgeon (XH. W) using a clear corneal incision, phacoemulsification, and implantation of IOLs in the capsular bag according to our previous studies [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, wound dehiscence does not seem to be related to clear corneal incision wound size. 17 In our study, we used manual clear corneal incisions positioned at the surgeon's discretion because of difficulty with wound predictability and intraoperative edema with FL incisions. The wound size was 2.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased corneal integrity caused by structurally weakening RK incisions poses a challenge to cataract surgeons. Zhang et al analyzed the outcomes of phacoemulsification using different sizes of clear corneal incision in post-RK eyes and found that dehiscence of the RK incisions could be closed successfully by injecting an air bubble into the anterior chamber at the end of surgery ( 53 ). Alternatively, Wang et al reported a smaller clear corneal incision or scleral tunnel incision might be safer ( 54 ).…”
Section: Emerging Challenges and A Paradigm Shift In The Management O...mentioning
confidence: 99%